2014
DOI: 10.5999/aps.2014.41.4.350
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of the Use of Absorbable and Nonabsorbable Materials as Internal Splints after Closed Reduction for Nasal Bone Fracture

Abstract: BackgroundThe authors sought to compare the use of the nonabsorbable polyvinyl alcohol sponge (PVA, Merocel) and absorbable synthetic polyurethane foam (SPF, Nasopore Forte plus) as intranasal splints after closed reduction of fractured nasal bones during the hospitalization period.MethodsThe medical records of 111 patients who underwent closed reduction for nasal bone fracture at Sanggye Paik Hospital, Inje University College of Medicine, from 2012 to 2013 were reviewed retrospectively. PVA (group A) or SPF (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Yi et al [ 2 ] reported that SPF shows a similar hemostatic effect and absorption of discharge as a packing material as compared to the traditional material, polyvinyl alcohol sponge (merocel) and showed less complications related to packing removal. Kim et al [ 3 ] reported decreased discomfort due to packing with maintaining nasal ventilation of the middle meatus by filling it with NAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yi et al [ 2 ] reported that SPF shows a similar hemostatic effect and absorption of discharge as a packing material as compared to the traditional material, polyvinyl alcohol sponge (merocel) and showed less complications related to packing removal. Kim et al [ 3 ] reported decreased discomfort due to packing with maintaining nasal ventilation of the middle meatus by filling it with NAS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of synthetic polyurethane foam (SPF) as an absorbable packing material can be a reasonable substitute for the traditional non-absorbable material [ 2 ], and the usefulness of the airway silicone splint with vaseline gauze has been proved [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The splint is held for 5 days to one week. It is believed that external splints will hold the bony segments in their new position and will help the skin envelope re-drape over its new structure [33][34][35].…”
Section: External Splint Applicationmentioning
confidence: 99%
“…reduction. 1 In general, nasal packing is performed after closed reduction. Nasal packing provides stability to the reduced bone fragment.…”
mentioning
confidence: 99%
“…Nasal bone fractures are a common kind of facial bone fractures. Surgical treatment is usually performed using closed reduction 1 . In general, nasal packing is performed after closed reduction.…”
mentioning
confidence: 99%